Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Văn học, 2004)
Vũ Thị Thường; Đỗ Quang Tiến; Trần Kim Trắc; Nguyễn Thị Ngọc Tú; Nguyễn Tuấn; Nhật Tuấn; Phan Tứ; Chu Văn.